Understanding Svara thought on Leadership by Top Administrators in a Changing World New Challenges in Political-Administrative Relations: Leadership, Administration, Political Administrative Relations - Fathurrohman, Deden (JAMAK, 2015)
Recently, administrators- in terms of leadership should become adapters who continuously adjust in the fluid environment in which they work as to fill their leadership responsibilities. It is very important to realistically grasp the status of administrators during each of these periods to have better understanding on how their circumstances are changing now. The future role will be different and complex, but there are always positive aspects of the change as well as negative ones.The focus of Svara writing is on top career administrators—local government CEOs and permanent secretaries in Europe and city/county managers and senior executives in the United States—who relate closely with top politicians (both top elected officials and political appointees) on the one hand, and the organization they more or less direct on the other. This condition can be seen as a way that could be the same or different if this compare to other countries, especially in Developing countries.There are so many challenges faced by administrators when they doing their duties. We are also aware of dichotomies between their roles in terms of political and administrative relations. It could be fruitful to find the harmonize way to manage this two relations. By understanding Svara writing and expanding by other writers, hopefully leadership a a changing world will be in a benefit way.This article want to have better understanding of what Svara writing on Leadership at the top administrators in term of political and administrative relations